2000
DOI: 10.1902/jop.2000.71.10.1583
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease Progression

Abstract: This study indicates that clinically significant progression of attachment loss in posterior tooth sites occurs as a frequent event in adult periodontitis. The modeling data also suggest that short-term (6 month) measures of periodontal disease progression greatly improve the ability to model attachment loss over a longer period in untreated periodontitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 34 publications
3
36
1
10
Order By: Relevance
“…If the gingival chronic inflammation is left, some teeth sites may develop periodontitis, characterized by irreversible alveo-lar bone loss. Recent evidence of untreated sites of periodontitis among adults showed that bone loss progressed at 1mm per 8.4 months on average 26 . The time it takes for gingivitis to progress to periodontitis is unknown and could take years; however, gingivitis is a necessary condition.…”
Section: Latency Time Of Oral Diseases -A Priori Hypothesesmentioning
confidence: 99%
“…If the gingival chronic inflammation is left, some teeth sites may develop periodontitis, characterized by irreversible alveo-lar bone loss. Recent evidence of untreated sites of periodontitis among adults showed that bone loss progressed at 1mm per 8.4 months on average 26 . The time it takes for gingivitis to progress to periodontitis is unknown and could take years; however, gingivitis is a necessary condition.…”
Section: Latency Time Of Oral Diseases -A Priori Hypothesesmentioning
confidence: 99%
“…It was demonstrated that results of subtraction radiolography were strongly associated with CAL relative to the frequency and pattern of disease activity measured by automated periodontal probes. 20,21 Despite the improved sensitivity and accuracy of the subtraction technique, detecting variations in bone still requires sequential observations over time.Microbiologic testing has been an important tool in determining the effects of therapy, predicting disease recurrence, and aiding in the choice of specific adjunctive antibiotics. 22 Although the gold standard in the field remains bacterial counting, a number of immune diagnostic methods were established to provide quantitative or semiquantitative estimates of oral microorganisms; these include direct or indirect immunofluorescent microscopy assays, flow cytometry, enzymelinked immunosorbent assay (ELISA), membrane assays and latex agglutination, multiplex polymerase chain reaction (PCR), and real-time PCR.…”
mentioning
confidence: 99%
“…It was demonstrated that results of subtraction radiolography were strongly associated with CAL relative to the frequency and pattern of disease activity measured by automated periodontal probes. 20,21 Despite the improved sensitivity and accuracy of the subtraction technique, detecting variations in bone still requires sequential observations over time.…”
mentioning
confidence: 99%
“…Whaites (1996) A escolha destes defeitos ocorreu em função da significante progressão da perda óssea, sobretudo nos dentes posteriores em adultos, fato este atestado por Reddy et al (2000). Também pelo fato que defeitos infra-ósseos são a principal causa de mobilidade e perda dos dentes.…”
Section: Metodologiaunclassified